Pseudohypoadrenalism, a subclinical cortisol metabolism disorder in hyperuricemia - Bao, Ruixia; Chen, Beibei; Pan, Jujie; Wang, Alexander; Yu, Haiyang; Chen, Qian; Zhang, Yi; Wang, Tao (Frontiers in Endocrinology, 2023)
Background Hyperuricemia is a known risk factor of lipid metabolism disorder. However, the mechanisms have not been fully understood. Methods The serum samples from hyperuricemia subjects were used to analyze the correlation between serum uric acid and clinical characteristics. Hyperuricemia mice induced by potassium oxonate (PO) and adenine were used to explore glucocorticoid metabolism. Results In hyperuricemia patients, the levels of serum uric acid were positively correlated with the levels of γ-glutamyltransferase, associated with a cortisol metabolism disorder. In hyperuricemia state, the adrenal glands failed to respond to adrenocorticotropic hormone properly, leading to low cortisol, but not corticosterone production, and decreased mRNA levels of aldosterone synthase, 11β-hydroxylase, and 3β-hydroxysteroid dehydrogenase 1, three key enzymes for cortisol synthesis. The expression of both hepatic 5α-reductase and renal 11β-hydroxysteroid dehydrogenase 2 was significantly reduced, which led to low cortisol clearance. We denominated this cortisol metabolism disorder in hyperuricemia as pseudohypoadrenalism (PHAL). Conclusion PHAL increased exposure to the bioavailable cortisol in the liver, leading to local amplification of the biological action of corticosteroids. Unregulated biosynthesis pathway of bile acid expanded bile acid pool, and further aggravated cholestatic liver injury.